Mejora de proceso en el área de compras en la compañía minera Aruntani - Erazo Mena, Diego (2023)
The main objective of this work is the implementation of improvements in the purchasing process in the Aruntani company due to the problem presented by the non-compliance of the purchasing area, such as the delay in the management of orders until the reception of the materials in the mine. These processes on average in 2018 required an average of 45 days from their creation. That is why the causes that determine this breach of purchase were analyzed and four proposals were determined that range from a policy of debugging, cataloging and normalization of inventory; supplier selection policy; of selection of purchasing strategy and the development of an information technology tool. In order to develop the proposals, industrial engineering tools were applied such as root-cause diagram, Ishikawa, Pareto, flow diagrams, criteria matrix, Porter forces, Internal and External Analysis. As a result of the implementation of the improvement, a time reduction was obtained in the logistics process from 45 days to only 20 days with a saving of 250,000 USD in the first six months debugging of non-standardized codes new procedures for the selection of suppliers and purchasing strategies, a new digital tool that improves communication between the user area in the mine and the buyer. Finally, the implementation had a nine-month schedule of activities for its execution and results. The budget was USD 19,800 for training, tools and consultancy.